The Sarashina Diary : a Woman's Life in Eleventh-Century Japan (Reader's Edition). - Sugawara no Takasue no Musume, 1008-; Arntzen, Sonja (La Vergne : Columbia University Press, 2018)
A thousand years ago, a young Japanese girl embarked on a journey from deep in the countryside of eastern Japan to the capital. Forty years later, with the long account of that journey as a foundation, the mature woman skillfully created an autobiography that incorporates many moments of heightened awareness from her long life. Married at age thirty-three, she identified herself as a reader and writer more than as a wife and mother; enthralled by fiction, she bore witness to the dangers of romantic fantasy as well as the enduring consolation of self-expression. This reader's edition streamlines Sonja Arntzen and Moriyuki Ito's acclaimed translation of the Sarashina Diary for general readers and classroom use. This translation captures the lyrical richness of the original text while revealing its subtle structure and ironic meaning, highlighting the author's deep concern for Buddhist belief and practice and the juxtaposition of poetic passages and narrative prose. The translators' commentary offers insight into the author's family and world, as well as the style, structure, and textual history of her work.
Intro; Table of Contents; Preface and Acknowledgments; Introduction; Sarashina Diary; Appendix 1. Family and Social Connections; Appendix 2. Maps; Appendix 3. List of Place Names Mentioned in the Sarashina Diary; Notes; Bibliography; Index.
Print version record.
eBooks on EBSCOhost
Keywords: Sugawara no Takasue no Musume, -- 1008- -- Diaries; Sugawara no Takasue no Musume, -- 1008-; Authors, Japanese -- Heian period, 794-1185 -- Diaries; Women -- Japan -- History -- To 1500.; Écrivains japonais -- 794-1185 (Époque de Heian) -- Journaux intimes; Femmes -- Japon -- Histoire -- Jusqu'à 1500.; LITERARY CRITICISM -- Asian -- General; Authors, Japanese -- Heian period; Women; Japan; To 1500; Diaries; History